Competitive detection of influenza neutralizing antibodies using a novel bivalent fluorescence-based microneutralization assay (BiFMA) - Baker, Steven F. (Vaccine, 2015)
Avian-derived influenza A zoonoses are closely monitored and may be an indication of virus strains with pandemic potential. Both successful vaccination and convalescence of influenza A virus in humans typically results in the induction of antibodies that can neutralize viral infection. To improve long-standing and new-generation methodologies for detection of neutralizing antibodies, we have employed a novel reporter-based approach that allows for multiple antigenic testing within a single sample. Central to this approach is a single-cycle infectious influenza A virus (sciIAV), where a functional hemagglutinin (HA) gene was changed to encode either the green or the monomeric red fluorescent protein (GFP and mRFP, respectively) and HA is complemented in trans by stable HA-expressing cell lines. By using fluorescent proteins with non-overlapping emission spectra, this novel bivalent fluorescence-based microneutralization assay (BiFMA) can be used to detect neutralizing antibodies against two distinct influenza isolates in a single reaction, doubling the speed of experimentation while halving the amount of sera required. Moreover, this approach can be used for the rapid identification of influenza broadly neutralizing antibodies. Importantly, this novel BiFMA can be used for any given influenza HA-pseudotyped virus under BSL-2 facilities, including highly pathogenic influenza HA isolates.